The Effect of Indigenous AMF Applications on The Morpho-Physiological Characteristics of Two Varieties of Shallots on Drought Stress Conditions - Eka Susila; Fri Maulina; Aswaldi Anwar; Auzar Syarif; Agustian Agustian (Journal of Applied Agricultural Science and Technology, 2023)
One of the limiting conditions for shallot plants to grow optimally is dry land conditions. Indigenous AMF application is one way to overcome this condition. This study aimed to determine the effect of indigenous AMF application on the morpho-physiological characters of two shallot varieties which are sensitive and tolerant to drought stress conditions. The study was carried out for 6 months on a wirehouse and laboratory scale. The Experiment used a completely randomized design with two factors. The first factor was varieties of shallots, i.e. Brebes (Sensitive) and Kuning (Tolerant) varieties of shallots. The second factor was the application of indigenous AMF which consisted of 5 levels i.e. Glomus sp1, Glomus sp2, Glomus sp3, a mixed those three isolates and control treatment (without application of AMF). The morpho-physiological observation parameters included header dry weight, root weight, and leaf proline content. From the observations, it can be concluded that under stressed conditions, the leaf proline content of the sensitive variety accumulated higher in the header than the tolerant variety, because the tolerant variety was better able to produce higher root and header weights when adapting than the sensitive. AMF inoculation did not show significant differences with the treatment without AMF inoculation on leaf proline. However, there was a tendency that inoculation of a mix of AMF isolates (Glomus sp1+Glomus sp2+ Glomus sp3) decrease the proline content in the leaves, both in sensitive and tolerant varieties so that plants are more resistant to drought stress.